2022
DOI: 10.1002/cche.10600
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selenium biofortification on bioaccessibility, antioxidant, and antimicrobial potentials of phenolic compounds in germinated black soybean (Glycine max (L.) Merr)

Abstract: Background and Objective Biofortification with inorganic selenium has become a key strategy to enhance selenium content in crops. This study aimed to investigate the changes of phenolic compounds and their effects on antimicrobial and antioxidant activities during in vitro digestion of selenium biofortified germinated black soybeans (GBS‐Se). Findings The bioaccessibility of total polyphenols and total flavonoids in GBS‐Se were significantly lower than those of germinated black soybeans (GBS). p‐Coumaric acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…For instance, J. Huang et al (2022) claimed that the bioaccessibility of TPC in BS was 21.50%, 38.75%, and 56.36% after oral, stomach, and small intestine digestions, respectively, suggesting a continual release of polyphenols during digestion; meantime, the bioaccessibility of total flavonoid content (TFC) was 8.96%, 17.07%, and 65.04%, respectively. Similarly, observed that the bioaccessibility of phenolic acids in BS was highest in the stomach (63.74%), followed by oral (62.53%) and intestine (39.89%).…”
Section: Bioavailability and Biotransformation Of Bioactive Compoundsmentioning
confidence: 99%
“…For instance, J. Huang et al (2022) claimed that the bioaccessibility of TPC in BS was 21.50%, 38.75%, and 56.36% after oral, stomach, and small intestine digestions, respectively, suggesting a continual release of polyphenols during digestion; meantime, the bioaccessibility of total flavonoid content (TFC) was 8.96%, 17.07%, and 65.04%, respectively. Similarly, observed that the bioaccessibility of phenolic acids in BS was highest in the stomach (63.74%), followed by oral (62.53%) and intestine (39.89%).…”
Section: Bioavailability and Biotransformation Of Bioactive Compoundsmentioning
confidence: 99%